Analisis Aspek Keuangan Bisnis Sambal Rujak Mbak Qom Dalam Prespektif Studi Kelayakan Bisnis - Khoiriyah, Umi Khozinatul; Rahman, Abdur (UMSurabaya Publishing, 2024)
Since the goal of the research is to review the general discussion of each piece that needs money and operating capital for the analysis of the evaluated investment, financial elements are crucial to examine. A business's viability may be evaluated using metrics like the Net Present Value (NPV), Payback Period (PP), Profability Index (PI), and Internal Rate of Return (IRR). Within the framework of field research, this study employs qualitative research methods. To gather information for this study, the proprietor of Sambal Rujak Mbak Qom was seen, spoken with, and recorded. First-hand accounts make up the data collection. The Payback Period (PP) for the Sambal Rujak Mbak Qom company is 7 weeks, or one month and three weeks, according to the feasibility analysis. Sambal Rujak Mbak Qom is considered to be a viable option based on the Net Present Value calculation, since the NPV value is greater than 0. Ultimately, the investment proposal is approved based on the Profitability Index computation, as the value of the index exceeds 1 based on feasibility criteria and the financial elements' outcomes. Keywords: business feasibility, financial aspects, payback period, net present value, profitability index Aspek keuangan penting untuk dianalisis karena tujuan studi adalah untuk menilai diskusi umum dari setiap elemen yang membutuhkan pendanaan dan modal kerja untuk analisis investasi yang dievaluasi. Kelangsungan hidup suatu usaha dapat dinilai dengan menggunakan kriteria seperti Profability Index (PI), Internal Rate of Return (IRR), Payback Period (PP), dan Net Present Value (NPV). Penelitian ini menggunakan metodologi penelitian kualitatif dalam konteks penelitian lapangan. Dalam rangka mengumpulkan data untuk penelitian ini, pemilik Sambal Rujak Mbak Qom diobservasi, diwawancarai, dan didokumentasikan. Data yang terkumpul merupakan catatan tangan pertama. Kelayakan usaha Sambal Rujak Mbak Qom menunjukkan bahwa Payback Period (PP) selama 7 minggu atau 1 bulan 3 minggu. Dari perhitungan Net Present Value, Sambal Rujak Mbak Qom dikatakan layak untuk dipilih karena nilai NPV > 0. Terakhir dari perhitungan Profitability Index, usulan investasi diterima karena nilai Profitability Index > 1 berdasarkan kriteria kelayakan, sesuai dengan hasil dari aspek keuangan. Kata Kunci: Kelayakan bisnis, aspek keuangan, payback period, net present value, profitability index